(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Voting is a constitutional part of governmental systems which gives the people of the nation the liberty to express their opinions. The contemporary system constitutes Electronic Voting Machines (EVM) that is a pile-up of data natively and centralized, making it implausible. Since the data is amassed locally over the EVM(s) prior to the election’s cessation, it could be hacked. Furthermore, there have been events of "polling booth hijacking" in some regions during the elections. Ethereum blockchain technology addresses concerns regarding integrity, security, and accessibility of current voting systems. Expanding e-voting into Ethereum based blockchain technology is one potential application of the emerging blockchain technology. This paper presents a decentralized, incognito, and limpid e-voting system named "DILE". It will escalate accessibility as the users could cast their votes without paying a visit to the polling booths. DILE makes practical and effective use of Ethereum’s blockchain technology and smart contracts for its implementation.